“Literature Review on Internet of Things” (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The unique and tricky phase of shrewd residential bundles in light of Internet of Things (IoT) is essentially controlled and dispersed. To give significant bits of knowledge into mechanical situations and bolster analysts, we should perceive the to be had choices and holes in this line of exploration. Along these lines, on this glance at, an outline is done to delineate examinations scene directly into a sound scientific classification.The axioms in the Information Technology is Internet of Things. The future is Internet of Things, which will transform the real world objects into intelligent virtual objects. The IoT aims to unify everything in our world under a common infrastructure, giving us not only control of things around us, but also keeping us informed of the state of the things. In Light of this, present study addresses IoT concepts through systematic review of scholarly research papers, corporate white papers, professional discussions with experts and online databases. Moreover, this research article focuses on definitions, geneses, basic requirements, characteristics and aliases of Internet of Things. The main objective of this paper is to provide an overview of Internet of Things, architectures, and vital technologies and their usages in our daily life. However, this manuscript will give good comprehension for the new researchers, who want to do research in this field of Internet of Things and facilitate knowledge accumulation in efficiently